Study of neutral-current four-fermion and ZZ production in e+e- collisions at √s = 183 GeV - Dova, María Teresa (1999)
A study of neutral-current four-fermion processes is performed using a data sample corresponding to 55.3 pb-1 of integrated luminosity collected by the L3 detector at LEP at an average centre-of-mass energy of 183 GeV. The neutral-current four-fermion cross sections for final states with a pair of charged leptons plus jets and with four charged leptons are measured to be consistent with the Standard Model predictions. Events with fermion pair masses close to the Z boson mass are selected in all observable final states and the ZZ production cross section is measured to be <mtext>σ</mtext><mtext>ZZ</mtext><mtext>=0.30</mtext><mtext>+0.22</mtext><mspace sp="0.2" width="2px" linebreak="nobreak" is="true"></mspace><mtext>+0.07</mtext><mtext>−0.16</mtext><mspace sp="0.2" width="2px" linebreak="nobreak" is="true"></mspace><mtext>−0.03</mtext> pb, in agreement with the Standard Model expectation. No evidence for the existence of anomalous triple gauge boson ZZZ and ZZγ couplings is found and limits on these couplings are set.